Recent Developments on the Synthesis of Sulfoxides via Sulfenate Anions - Saito, Fumito (Synthesis, 2023)
Since the early 2000s, novel synthetic methods for the preparation of sulfoxides have emerged that involve sulfenate anions as sulfur nucleophiles. This short review showcases key advances in these sulfenate protocols, including catalytic enantioselective alkylation and arylation, and provides future directions for this research field.1 Introduction2 Precursors of Sulfenate Anions3 Organocatalytic Enantioselective Alkylation of Sulfenate Anions4 Palladium-Catalyzed Arylation of Sulfenate Anions5 Coupling of Sulfenate Anions with Hypervalent Iodine Reagents6 Conclusions and Outlook
Keywords: sulfoxides; sulfenate anions; organocatalysis; palladium; hypervalent iodine reagents